PERBEDAAN KUALITAS PELAYANAN KEPERAWATAN TERHADAP PASIEN PENERIMA BANTUAN IURAN DAN PASIEN BUKAN PENERIMA BANTUAN IURAN - Rattu, Prisilia; Warouw, Herman; Hamel, Rivelino Spener (JURNAL KEPERAWATAN, 2015)
Abstract: Background quality of nursing services as an indicator of the success of nursing services at the hospital. Patients as nursing care service users who require nursing care according to their rights in this respect patients receiving tuition assistance that is relatively poor and the underprivileged who are paid directly by the Goverment and the patient is not receiving tuition assistance that are not classified as poor who are paid by employers, workers and participants concerned. This study aims see the difference in the quality of nursing services to patients receiving tuition assistance and patients not receiving tuition assistance and to look the quality of nursing services to patients receiving tuition assistance dan patients not dues. The design study is a comparative descriptive study. Respondents amounted to 80 people. Taken using purposive sampling technique using a questionnaire about the quality of nursing services that include tangible, reliability, responsiveness, assurance, empathy. Later in the analysis using SPSS program using the chi square at 95% significance level (α = 0,05). With the results most respondents patients receiving tuition assistance recipients and patients not receiving tuition assistance say it’s a good, with α = 0,141. In conclusion there was no difference un the quality of nursing services to patients receiving tuition assistance and patients not receiving tuition assistance. Keywords: quality of service, nursing service, tuition assistance Abstrak: Latar belakang Kualitas pelayanan keperawatan sebagai indikator keberhasilan pelayanan perawat di rumah sakit. pasien sebagai pengguna jasa pelayanan keperawatan menuntut pelayanan keperawatan yang sesuai haknya dalam hal ini pasien penerima bantuan iuran yaitu tergolong fakir miskin serta kurang mampu yang dibayar langsung oleh Pemerintah dan pasien bukan penerima bantuan iuran yaitu tidak tergolong fakir miskin yang dibayar oleh pemberi kerja, pekerja dan peserta yang bersangkutan. Tujuan untuk melihat perbedaan kualitas pelayanan keperawatan terhadap pasien penerima bantuan iuran dan pasien bukan penerima bantuan iuran dan guna memperoleh gambaran kualitas pelayanan keperawatan terhadap pasien penerima bantuan iuran dan pasien bukan penerima bantuan iuran. Desain penelitian yang digunakan yaitu penelitian deskriptif komparatif. Responden berjumlah 80 orang. Diambil menggunakan teknik purposive sampling dengan menggunakan kuesioner tentang kualitas pelayanan keperawatan yang meliputi tangible, reliability, responsiveness, assurance, empaty. Kemudian dianalisis menggunakan program SPSS menggunakan uji chi square pada tingkat kemaknaan 95% (α = 0,05). Hasil pasien penerima bantuan iuran dan pasien bukan penerima bantuan iuran mengatakan sudah baik, dengan α = 0,141. Kesimpulan tidak ada perbedaan kualitas pelayanan keperawatan terhadap pasien penerima bantuan iuran dan pasien bukan penerima bantuan iuran. Kata kunci: kualitas pelayanan, pelayanan keperawatan, bantuan iuran